Employment contribution of private equity and venture capital in Europe - Ann-Kristin Achleitner; Oliver Klöckner (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2005)
Over the past ten years, private equity and venture capital have played an increasingly important role in the European economy. In parallel to the increase in investments, contribution of the private equity and venture capital industry to employment in Europe has grown. Against this background, the European Ventura Capital and Private Equity Association has commissioned the Center for Entrepreneurial and Financial Studies (CEFS) at the Technische Universität München to undertake a research study on the contribution of the private equity and venture capital sector to European employment. 201 private equity and venture capital-backed companies participated in the pan-European survey. The study has found that private equity and venture-backed companies employed between 4.8 and 6.4 million people in Europe in 2004. European private equity and venture capital-financed companies created 1 million jobs between 2000 and 2004. 420,000 new jobs were created in buy-out financed companies and 630,000 new jobs in venture-backed companies within this period. Employment grew in buyout-financed companies by 2.4% and in venture-backed companies by 30.5% on average per year between 1997 and 2004.
Keywords: M13; G24; E24; 330; venture capital; private equity; employment; economic impact; Risikokapital; Private Equity; Beschäftigungseffekt; Europa